Analysis of the Dispute of Unlawful Acts in the Land Sale and Purchase Agreement - Pakaya, Rafi Hidayahtullah; Narendra, Ananda Chaya; Ivanda, M Nauval; Andryanto, Ary; Ardiansyah, M Rizky (Interdisciplinary Social Studies, 2021)
The sale and purchase of land in this study leads to the rights of a land. From a legal point of view, buying and selling land is not about the land being traded, but the right to use the land. Regulations regarding the transfer of land rights are regulated in PP No. 34 of 1997 Article 32 paragraph (2) which reads: “Under certain conditions as determined by the Minister, the Head of the Defense Agency can register the transfer of ownership rights to a parcel of land, which is carried out between Indonesian citizens individually with evidence of a deed not made. This study aims to analyze the dispute of unlawful acts in the land sale and purchase agreement. This type of research is normative legal research that focuses on applicable legal norms and the study of legal norms is carried out by examining secondary data as the main data, while primary data as supporting data. This normative legal research is viewed from several aspects, such as aspects of theory, philosophy, comparison, general explanation, composition, and so on. The UUPA does not clearly explain what is meant by buying and selling land, but agrarian law uses a system and legal principles. The customary law used is the customary law that applies ndi s adapted nationally and follows modern developments. In essence, buying and selling land is the transfer of land rights from the seller to the buyer, so that the buyer can use the land according to its function. According to the UUPA, there are various types of land rights that can be transferred, namely property rights, use rights and building rights.